A Study on the Influence of Induced Water Stress on Seeds Germination and Seedlings Growth of Silybum marianum - AI-Aiwani, M. A. M (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of water stress induced by using polyethylene glycol (PEG-6000) on germination of seeds and growth of seedlings of Silybum marianum was studied. Two concentrations of PEG were used to get two water stresses (-0.4 & -0.8 bar) as well as the control for comparison. The results showed a significant decrease (P<0.05) in germination ratio compared with the control. The ratio did not slow down to less than 50% which indicates the ability of the seeds to resist water stress to some extent. Also, a significant decrease (P<0.05) in the length of shoot and root was observed compared with the control. This plant showed an ability to recover when the water stress was broken and the shoot recovery was larger to some extent than the root.